(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
This article explores the crucial role of language, particularly English terminology, in environmental reporting within mass media discourse. It delves into the intricate relationship between language, communication, and environmental issues, highlighting how the choice and use of terminology shape public perception, policy formulation, and societal responses to environmental challenges. By analyzing the linguistic dimension of environmental reporting, the article aims to shed light on the power dynamics inherent in the selection and framing of environmental narratives. Through a multidisciplinary approach drawing from linguistics, media studies, and environmental science, it examines the nuances of language use, including terminology adoption, linguistic framing, and discursive strategies employed by media outlets. Additionally, the article explores the implications of linguistic choices on audience comprehension, engagement, and action regarding environmental issues. Ultimately, it underscores the importance of linguistic awareness and precision in environmental reporting to foster informed discourse, policy deliberation, and collective action toward sustainability.